Faunal remains from the upper levels of Los Carneros cave (Alto Chacabuco, XI Region, Chile) - Mena Larraín, Francisco; López Mendoza, Patricio (Revista Chilena de Antropología, 2015)
The results of the zooarchaeological and taphonomical analysis of the materials recovered at the upper levels from Cueva Los Carneros are presented. The archaeofaunal record is shaped by a diversity of taxa that represent the mosaic of microenvironments around the site. In effect, CLC corresponds to a locality characterized by diversified hunt, in which the species with major frequency of capture and consumption correspond to several rodents, Lama guanicoe, Zaedyus pichiy, Rhea pennata, Hippocamelus bisulcus and birds, among others. These are joined by many taxa (like rodents and lizards) that were deposited by natural and antrophic agents integral to the dynamics of all rock shelters. Although archaeofaunal data do not clearly point to a summertime occupation, whereas the frequency of gunanacos, huemules and other taxa suggest hunting activities geared towards greasemedulla consumption and the transport of ther anatomical units within a patterned mobility strategy.